Dynamics of Genotypic and Phenotypic Antibiotic Resistance in a Conventional Wastewater Treatment Plant in 2 Years - Shin, Hanseob; Kim, Yeonghyeon; Raza, Shahbaz; Unno, Tatsuya; Ryu, Song-Hee; Hur, Hor-Gil (Frontiers in Microbiology, 2022)
Wastewater treatment plants (WWTPs) are considered as a sink and a source of antibiotic resistance. In this study, we applied both of culture dependent and SmartChip-based culture independent approaches for investigation of antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) at Jungnang (JN), which is located in the Han River, Seoul, South Korea for two years of 2017 and 2018. The JN WWTP reduced diversity and abundance of ARB and ARGs, but was not sufficient for removing them all. Interestingly, through the treatment process in the JN WWTP, the composition of diverse multidrug resistant (MDR) bacteria were concentrated mainly into some genera of Gammaproteobacteria class (Citrobacter, Escherichia-Shigella, and Stenotrophomonas), which could be key carriages to spread ARGs into the environments. In addition, SmartChip analyses showed that the relative abundance and the number of ARGs were significantly decreased from the influents to the effluents in both 2017 and 2018. SmartChip analyses for two years also allowed to notify core ARGs in the influents, and the effluents with the presence of clinically-relevant core ARGs, such as vanC, blaOXA, and blaNDM, which persisted the treatment process. Considering diverse bacterial mechanisms for exchanging and transferring ARGs, the occurrence of MDR bacteria and core ARGs could be a source for blooming of the antibiotic resistome in the WWTP and nearby environments.